PENGARUH FAKTOR INTERNAL DAN EKSTERNAL PADA AUDIT DELAY - Karang, Ni Made Dwi Umidyathi; Yadnyana, I Ketut; Ramantha, I Wayan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2015)
This research aims to reveal (1) the effect of company size on audit delay, (2) the effect of company’s profitability on audit delay, (3) the effect of solvability on audit delay, (4) the effect of auditor quality on audit delay and (5) the effect of auditor opinion on audit delay of companies listed on Indonesian Stock Exchange. The data population used in this research are all the companies that are listed in BEI. The sample were taken randomly using Slovin equation, as a result, there were 115 companies choosen from the population. The data were analise using double regresion analysis. The research result indicated that (1) company size has positive and significant effect on audit delay, (2) profitability has negative effect on audit delay, (3) solvability has positive and significant effect on audit delay, (4) ) auditor quality has negative effect on audit delay and (5) ) auditor opinion has negative effect on audit delay.
Keywords: Ukuran Perusahaan; Profitabilitas; Solvabilitas; Kualitas Auditor; Opini Auditor; Audit Delay